Geophysical investigation of the effects of refuse dumpsites on the quality of groundwater in some major towns in Niger state, Nigeria - Tsepav, Matthew Tersoo; Usman, T Y; Alfa, B; Worogi, A I; Adamu, Y; Abdullahi, M. (Journal of Physics: Theories and Applications, 2023)
This study was carried out to investigate the effects of refuse dumpsites on the quality of groundwater in some major towns in Niger State, Nigeria. A total of sixty (60) Vertical Electrical Soundings (VES) was conducted across fifteen (15) dumpsites within the study areas; twenty (20) VES at each of the three (3) dumpsites of Lapai, Bida and Paiko using Schlumberger configuration to investigate the possibility of contamination of groundwater in the areas. The resistivity data were collected using G41 Resistivity Meter and interpreted using IPI2Win Software. The results revealed four geo-electrical layers. The resistivity values of the Aquifer layers of Lapai dumpsites ranged from 136 Ωm to 681 Ωm, with the thickness ranging between 2.82 - 8.77 m at the depth of 4.21 – 10.90 m at Engr. A. A. Kure dumpsite. At Malle dumpsite, the thickness range was (1.10 – 4.39) m and the depth at 5.27 – 12.70 m. The resistivity values of the aquifer layers at Bida dumpsites ranged from 161.10 Ωm to 223 Ωm, with the thickness ranging between 4.86 and 11.00 m at the depths of 7.65 – 12.70 m while at Mayaki Ndajiya dumpsite, the thickness range was 4.91 – 23.46 m at the depth of 6.84 – 25.57 m. Also the resistivity values of the aquifer layers of Paiko dumpsites ranged from 20.90 Ωm to 110 Ωm with thicknesses ranging from 2.33 to 14.00 m at the depth range of between 3.85 and 15.50 m at Gidan Marafa dumpsite while the thickness range was from 3.19 – 9.04 m at the depth of 6.70 – 14.14 m at Angwan Akimi dumpsite. These values were used to compute the Dar Zarrouk parameters which indicate aquifer protectivity. The protective capacity of the over burden rock materials at Lapai dumpsites ranged from 0.010 – 0.076 Siemens, while at Bida dumpsites it ranged 0.009 – 0.152 Siemens and at Paiko dumpsites it ranged between 0.025 – 0.046 Siemens. The low protective features observed in the Aquifer zones of Lapai, Bida and Paiko dumpsites indicated the possibility of leachate migration from the waste dumpsites infiltrating into the aquifers and polluting the groundwater. It is evident, from the results of this geophysical survey that the water in the study areas of Lapai, Bida and Paiko could be polluted leading to water related diseases.